2002
DOI: 10.1109/jqe.2002.1017597
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Q factor in photonic crystal microcavities

Abstract: Abstract-We express the quality factor of a mode in terms of the Fourier transforms of its field components and prove that the reduction in radiation loss can be achieved by suppressing the mode's wavevector components within the light cone. Although this is intuitively clear, our analytical proof gives us insight into how to achieve the factor optimization, without the mode delocalization. We focus on the dipole defect mode in free-standing membranes and achieve 10 4 , while preserving the mode volume of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
145
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(150 citation statements)
references
References 20 publications
5
145
0
Order By: Relevance
“…The fourier space analysis [3][4], the multi-pole cancelation [5], and the mode matching mechanism [6][7] [8] have been developed to explain the origin of high Qs. The design of PhC cavities, however, is typically based on extensive parameter search and optimization [9]- [13], also known as intuitive design.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fourier space analysis [3][4], the multi-pole cancelation [5], and the mode matching mechanism [6][7] [8] have been developed to explain the origin of high Qs. The design of PhC cavities, however, is typically based on extensive parameter search and optimization [9]- [13], also known as intuitive design.…”
mentioning
confidence: 99%
“…As shown previously [3][16], scattered power (P sc ) can be expressed as an integral of spatial fourier frequencies within a light cone, calculated over the surface above the cavity:…”
mentioning
confidence: 99%
“…We first perform a full electromagnetic study of these microcavities with a 3D frequency-domain modal method 10 and emphasize the impact of hole tuning on the Q factors of cavities with several N values. Currently, the theoretical analysis 5,11,12 of PC slab microcavities relies on a complete resolution of the electromagnetic problem with 3D Finite-Difference-Time-Domain methods, followed by an analysis of the cavity-mode pattern through a Fourier (or momentum-space) decomposition method. The approach we develop here is radically different.…”
mentioning
confidence: 99%
“…A tremendous amount of progress has been made both in optimizing cavity properties such as the quality (Q)-factor [1]- [3] and mode volume as well as in developing interesting applications that are intrinsically enabled through a nanoscale dielectric form factor [4]- [6]. Early work in this field showed that localized defect modes can be created by perturbing the periodicity of a photonic lattice, creating highly customizable nanocavities with simple control over mode field patterns, radiation profiles, spectral positioning, and photon lifetime [7], [8].…”
mentioning
confidence: 99%